Evolution of durum wheat breeding in Italy - Porceddu E.; Blanco A. (Proceedings of the International Symposium on Genetics and breeding of durum wheat, 2014)
The paper reports on the scientific effort for improving durum wheat production and quality made by Italian breeders and geneticists by exploiting the rich reservoir of genetic variation present in the Mediterranean area and in the germplasm introduced from distant geographical areas, as well as in attempting to understand the genetic control of agronomically and technologically important traits.
International Symposium : Genetics and Breeding of Durum Wheat, 2013/05/27-30, Rome (Italy)